Bioactive natural products from marine sponges belonging to family Hymedesmiidae - Elgoud Said, Asmaa Abo; Mahmoud, Basma Khalaf; Attia, Eman Zekry; Abdelmohsen, Usama Ramadan; Fouad, Mostafa Ahmed (RSC advances, 2021)
Natural products of marine origin exhibit extensive biological activities, and display a vital role in the exploration of new compounds for drug development. Marine sponges have been reported at the top with respect to the discovery of biologically active metabolites that have potential pharmaceutical applications. The family Hymedesmiidae belonging to the Demospongiae class includes ten accepted genera, of which four genera were explored for their bioactive metabolites, namely Phorbas , Hamigera , Hemimycale , and Kirkpatrickia . Genus Phorbas has received more attention due to the isolation of various classes of compounds with unique structures mainly diterpenes, alkaloids, sesterterpenes, and steroids that exhibited diverse biological activities including: antiviral, antimicrobial, and anti-inflammatory, whereas anticancer compounds predominated. This review focuses on the isolated secondary metabolites from family Hymedesmiidae with their biological potential and covers the literature from 1989 to 2020. Natural products of marine origin exhibit extensive biological activities, and display a vital role in the exploration of new compounds for drug development.